P38α MAPK disables KMT1A-mediated repression of myogenic differentiation program. Issue 1 (December 2016) - Chatterjee, Biswanath; Wolff, David; Jothi, Mathivanan; Mal, Munmun; Mal, Asoke
Abstract Background Master transcription factor MyoD can initiate the entire myogenic gene expression program which differentiates proliferating myoblasts into multinucleated myotubes. We previously demonstrated that histone methyltransferase KMT1A associates with and inhibits MyoD in proliferating myoblasts, and must be removed to allow differentiation to proceed. It is known that pro-myogenic signaling pathways such as PI3K/AKT and p38α MAPK play critical roles in enforcing associations between MyoD and transcriptional activators, while removing repressors. However, the mechanism which displaces KMT1A from MyoD, and the signals responsible, remain unknown. Methods To investigate the role of p38α on MyoD-mediated differentiation, we utilized C2C12 myoblast cells as an in vitro model. p38α activity was either augmented via overexpression of a constitutively active upstream kinase or blocked via lentiviral delivery of a specific p38α shRNA or treatment with p38α/β inhibitor SB203580. Overexpression of KMT1A in these cells via lentiviral delivery was also used as a system wherein terminal differentiation is impeded by high levels of KMT1A. Results The association of KMT1A and MyoD persisted, and differentiation was blocked in C2C12 myoblasts specifically after pharmacologic or genetic blockade of p38α. Conversely, forced activation of p38α was sufficient to activate MyoD and overcome the differentiation blockade in KMT1A-overexpressing C2C12 cells. Consistent with this finding, KMT1A phosphorylation during C2C12 differentiation correlated strongly with the activation of p38α. This phosphorylation was prevented by the inhibition of p38α. Biochemical studies further revealed that KMT1A can be a direct substrate for p38α. Importantly, chromatin immunoprecipitation (ChIP) studies show that the removal of KMT1A-mediated transcription repressive histone tri-methylation (H3K9me3) from the promoter of theMyogenin gene, a critical regulator of muscle differentiation, is dependent on p38α activity in C2C12 cells. Elevated p38α activity was also sufficient to remove this repressive H3K9me3 mark. Moreover, ChIP studies from C2C12 cells show that p38α activity is necessary and sufficient to establish active H3K9 acetylation on theMyogenin promoter. Conclusions Activation of p38α displaces KMT1A from MyoD to initiate myogenic gene expression upon induction of myoblasts differentiation.